Radon concentrations in dwellings of Baghdad city- Iraq - Ali , Kamal K.; Mohammed, Aamir A.; Ahmad , Thuraya M.; Ibrahim, Safaa K. (Iraqi Journal of Science, 2022)
In this study, radon concentrations were measured in dwellings at specified locations in Baghdad city using ionization chamber radon monitor (ALPHA GUARD PQ2000 PRO). The measurements were carried out at different locations of these dwellings (living rooms, bed rooms, bath rooms, and kitchens). The results of the survey showed that the overall minimum, maximum average and mean average radon concentrations in dwellings were 5.77±0.73 Bq/m3, 23.27±13.57 Bq/m3, and 10.67±4.14 Bq/m3 respectively. The lowest average radon was found in (Ameryia) city, while the highest average radon concentration was found in (Kadmiya) city. Also, the results showed that the highest average radon concentration was found in the kitchens, while the lowest average radon concentration was found in the living rooms. The maximum annual effective dose in dwelling in Baghdad city in current study is 0.59 mSv.